Compound corrosion inhibitor for continuous metal coiled material and treatment process of compound corrosion inhibitor

By forming an organic-inorganic collaborative film layer on the surface of the aluminum alloy coil through a composite corrosion inhibitor system, the problems of uneven film formation and insufficient functional division of labor of the existing aluminum alloy coil in a chloride ion environment are solved, and efficient corrosion protection effect is achieved.

CN120330708AActive Publication Date: 2025-07-18ZHONGKE WEIMIAO (QINGDAO) EQUIP TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510837970.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-07-18
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

The existing aluminum alloy coil corrosion inhibitor has poor protection effect in the corrosion environment where chloride ions exist, and is uneven in film formation, which is prone to pitting. It is difficult for existing processes to achieve the functional division of adsorption and film formation, resulting in fluctuations in the mass of the film layer.

Method used

The composite corrosion inhibitor system is adopted, including an adsorption sustained release system and an induced film formation system, and the aluminum alloy coil is treated in two tanks respectively. The mixture of sodium glutamate and sodium glycine is used to form an organic protective layer, and the potassium zirconate and complexing control agent are used to form an inorganic conversion film. The combination of surfactant and inhibitor is combined to optimize the pH value and concentration conditions to achieve multi-component synergy.

Benefits of technology

It significantly improves the initial corrosion-blocking ability of aluminum alloy coils, builds a dense and stable inorganic conversion film, enhances the continuity and stability of the film layer, extends the service cycle, and adapts to the protective performance in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120330708A_ABST
    Figure CN120330708A_ABST
Patent Text Reader

Abstract

The invention discloses a compound corrosion inhibitor for a continuous metal coiled material and a treatment process of the compound corrosion inhibitor, and relates to the technical field of corrosion inhibitors and treatment. The corrosion inhibitor is composed of an adsorption slow-release system solution and an induction film-forming system solution, and the surface of the metal coiled material is subjected to step-by-step treatment in independent process tanks. The adsorption slow-release system comprises a main corrosion inhibitor, an auxiliary corrosion inhibitor, an inhibitor and a surfactant, and the induced film-forming system comprises a metal salt and a complexing control agent which are respectively used under set pH and concentration conditions. The pre-adsorption system is used for complexing and covering active sites on the metal surface, so that the initial corrosion reaction is obviously inhibited; and the film forming system is induced to generate a compact and stable inorganic film layer on the basis, so that the interface impedance and the corrosion resistance are improved. By optimizing the compounding proportion, the synergistic effect of the components is realized, and the structural integrity and protection performance of the film layer are improved; component interference is avoided by adopting double-groove step-by-step treatment, and the continuity and stability of the film layer are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of corrosion inhibitors and treatment technologies, and particularly to a compound corrosion inhibitor for continuous metal coils and a treatment process thereof. Background Art

[0002] With the advancement of the trends of industrial lightweight and green manufacturing, aluminum and its alloys have been widely used in many industrial fields such as aerospace, automotive manufacturing, rail transit, and electronic products due to their excellent specific strength, corrosion resistance, and recyclability, and particularly play an important role in the production and surface treatment of continuous metal coils. Aluminum alloys are regarded as ideal structural and coating materials due to their natural passivation ability; however, in a corrosion environment where halogen ions such as chloride ions exist, their native oxide film is easily damaged, and rapid pitting corrosion expansion occurs after exposing fresh metal, seriously affecting their service life and interface stability, especially in humid or high-salt environments. Therefore, developing an efficient and environmentally friendly corrosion inhibitor system and its continuous treatment process is of great significance for improving the protection level of aluminum alloy coils.

[0003] Currently, the surface protection methods applied to aluminum alloys include processes such as anodic oxidation, phosphating, chromate passivation, organic / inorganic composite coatings, and corrosion inhibitor solution treatment. Among them, the traditional chromate system has excellent corrosion resistance and film-forming ability, but there are significant environmental protection hazards; although anodic oxidation can form a dense film layer, the process cycle is long, the energy consumption is high, and it is difficult to adapt to a high-speed continuous treatment system; while the organic or inorganic corrosion inhibitor method has been widely studied due to its environmental friendliness and process simplicity, but generally has the following technical problems: First, the existing corrosion inhibitors are mainly single-component, lacking the ability to complex with the aluminum alloy surface directionally, with low adsorption efficiency, uneven film layer coverage, and unable to effectively seal micropores and grain boundary sites; Second, some corrosion inhibitor films have a loose structure or many defects, poor resistance to chloride ion penetration, and pitting corrosion is easy to expand under the film, resulting in local failure; Third, in a multi-component coexistence system, competitive adsorption and deposition interference between corrosion inhibitors and film-forming ions often occur, affecting the integrity of the film layer structure and functional synergy. In addition, the existing industrial applications mostly adopt a single-tank integrated treatment mode, which is difficult to effectively achieve the functional division of adsorption components and film-forming components, resulting in a decrease in film-forming efficiency and fluctuations in film layer quality, restricting the engineering adaptability and stability of the corrosion inhibition technology for aluminum alloy coils.

[0004] Therefore, there is an urgent need to develop a compound corrosion inhibition and protection system suitable for continuous treatment of aluminum alloy coils. This system should be able to rapidly form a multi-component synergistic adsorption layer on the metal surface, preferentially seal active sites, and inhibit the expansion of initial pitting corrosion. On this basis, it induces the deposition of a conversion film layer with a dense structure and strong bonding force, enhances the interfacial impedance, and inhibits the chloride ion penetration path. At the same time, through the design of the separate tank process, the functions of adsorption and film formation should be carried out step by step to avoid interference between components and improve the integrity and uniformity of the film layer. This solution should have the advantages of being green and environmentally friendly, having strong process controllability, and being adaptable to the industrial continuous treatment rhythm, effectively improving the electrochemical stability and medium- and long-term corrosion protection ability of aluminum alloy coils. Summary of the Invention

[0005] The technical concept of the present invention is based on the design concept of green corrosion inhibitors and the optimization strategy of industrial continuous treatment paths. It breaks through the problems existing in the existing corrosion inhibition systems, such as the weak corrosion inhibition ability of single components, poor film formation compactness, and insufficient compatibility with continuous processes, and provides an efficient composite corrosion inhibition and protection system constructed by the synergistic action of an organic adsorption-inorganic film formation dual mechanism.

[0006] The specific solution is as follows: A compound corrosion inhibitor for continuous metal coils, which is prepared from an adsorption and slow-release system solution and an induced film formation system solution: The adsorption and slow-release system solution includes the following components: The main corrosion inhibitor is a mixture of sodium glutamate and sodium glycine, with a concentration of 0.06 - 0.2 mol / L The auxiliary corrosion inhibitor, with a concentration of 0.005 - 0.05 mol / L The inhibitor, with a concentration of 0.001 - 0.02 mol / L The surfactant, with a concentration of 0.001 - 0.01 mol / L The rest is deionized water, and the pH of the solution is adjusted to 7.0 - 7.5; The induced film formation system solution includes the following components: Potassium zirconate, with a concentration of 0.005 - 0.015 mol / L The complexation control agent, with a concentration of 0.001 - 0.01 mol / L The rest is deionized water, and the pH is adjusted to 4.0 - 5.0.

[0007] Preferably, the adsorption and slow-release system solution and the induced film formation system solution are sequentially applied to the first tank and the second tank in the continuous treatment process of the metal coil to form a composite corrosion inhibition film layer constructed by organic-inorganic coordination.

[0008] Preferably, the auxiliary corrosion inhibitor is one of sodium citrate, sodium malate, and sodium hypophosphite, which is used to further adjust the complexation site density and the metal ion capture ability.

[0009] Preferably, the inhibitor is one of benzotriazole, EDTA, and sodium tripolyphosphate, which is used to block the anodic reaction or the chloride ion erosion path, and is used to improve the adsorption uniformity and the wettability of the coil surface.

[0010] Preferably, the surfactant is one of sodium dodecyl sulfonate, sodium dodecyl benzene sulfonate, and cocamidopropyl betaine, ensuring that the amino acid-based corrosion inhibitor fully functions in a stable complex adsorption state.

[0011] Preferably, the molar ratio of sodium glutamate to sodium glycine is 2:1 - 5:1.

[0012] The present invention also provides a compound corrosion inhibitor treatment process for continuous metal coils, including the following steps: (1) Coil pretreatment: The metal coil is successively subjected to alkali washing and degreasing, acid washing and neutralization, and deionized water rinsing; (2) Adsorption and slow-release system solution treatment: The coil output from step (1) enters the adsorption and slow-release system solution tank for immersion treatment; (3) Induced film formation with the induced film formation system solution: The coil output from step (2) enters the induced film formation system solution tank; (4) The coil output from step (3) is dried with hot air, cooled, and wound up.

[0013] Preferably, the adsorption and slow-release system solution and the induced film formation system solution in the corrosion inhibitor are prepared from the above raw materials.

[0014] Preferably, the treatment temperature in step (2) is 35 - 40 °C, and the immersion time is 60 - 90 seconds; Preferably, the treatment temperature in step 3 is 40 - 50 °C, and the treatment time is 30 - 60 seconds; Preferably, the hot air temperature in step (4) is 80 - 90 °C, and the wind speed is 2 - 5 m / s. Preferably, the metal coil is any one of AA3003, AA5005, and AA6061 aluminum alloy coils.

[0015] Preferably, for coil pretreatment: The aluminum alloy coil is successively subjected to degreasing, acid washing and neutralization, and deionized water rinsing. Preferably, the degreasing solution is a mixed solution of 5 wt% NaOH and 1 wt% Na3PO4, the treatment temperature is 55 °C, and the treatment time is 90 seconds; the pickling solution is 1 wt% HNO3, and the treatment time is 20 seconds to ensure a clean and active surface state.

[0016] Preferably, the coil thickness is 0.5 - 2 mm, and the linear velocity is 3 - 8 m / min.

[0017] Beneficial effects brought by the technical solution provided by the present invention: Improve the initial corrosion blocking ability By adopting an amino acid adsorption corrosion inhibition system composed of sodium glutamate and sodium glycine, the present invention realizes rapid complexation adsorption on the surface of aluminum alloy in the first treatment tank, forms a stable organic protective layer, thereby closing the defect and microcrack regions of the oxide film at the initial stage of corrosion, and blocking the erosion paths of corrosion ions such as Cl ions. In-situ corrosion observation results show that the adsorption layer can significantly reduce the number and reaction rate of the initial electrochemical active regions, reduce the generation of corrosion products, and improve the integrity of the interface structure.

[0018] Construct a dense and stable inorganic conversion film In the second treatment tank, potassium zirconate and the complexation control agent cooperate to induce the hydrolysis and deposition of Zr ions in the region of the native oxide film and the adsorption layer on the aluminum substrate, generating an inorganic conversion film mainly composed of Zr-O-Al or Zr-O-C. The film layer structure is continuous and dense, firmly combined with the substrate, and significantly improves the interface resistance and passivation performance. Electrochemical impedance spectroscopy tests show that the film resistance of the implemented sample is higher than that of the comparative sample, and the interface capacitance decreases, indicating that the film layer has good corrosion resistance stability.

[0019] Compound design to enhance the synergistic effect of components Optimize the molar ratio of sodium glutamate and sodium glycine to enhance the adsorption uniformity in the micro-defect region of the aluminum alloy oxide film and improve the interfacial reaction activity with Zr ions; under the synergistic action with the potassium zirconate induction system, a multi-layer protective film integrating organic and inorganic can be formed. Polarization curve results show that at this compound ratio, the corrosion current density is the lowest and the corrosion inhibition efficiency is the best, verifying that the component ratio is closely related to the film layer quality.

[0020] Two-step treatment in two tanks to achieve interfacial function synergy The adsorption and film formation are processed in separate tanks, which can avoid the reaction interference between corrosion inhibition components, ensure the complete retention of the adsorption layer, and improve the directional deposition efficiency of Zr ions. This process method makes the conversion film denser and has fewer defects, effectively improves the film layer continuity and thickness uniformity, enhances the coverage ability of Al ion dissolution and corrosion-induced points, and overall improves the protective performance of the film layer functional structure.

[0021] Extend the service life and environmental adaptability The corrosion inhibition film layer constructed by the present invention maintains good structural stability and durability in a multi-cycle humid and hot or salt spray environment, and no obvious film layer peeling, blistering or corrosion product precipitation occurs. Compared with the untreated sample, the long-term denseness and surface uniformity of the film layer are better, verifying its medium- and long-term protection efficiency in the continuous production of aluminum alloy coils and complex service environments. Description of the drawings

[0022] Figure 1Potentiodynamic polarization curves of the examples and comparative examples of the present invention; Figure 2 Fitted data of the alternating current impedance spectra of the examples and comparative examples of the present invention - Nyquist plot; Figure 3 Fitted data of the alternating current impedance spectra of the examples and comparative examples of the present invention - Bode plot; Figure 4 In-situ optical microscope images of the blank sample of the present invention, (a) uncorroded; (b) corroded for 1 minute; (c) corroded for 5 minutes; (d) corroded for 10 minutes; (e) corroded for 15 minutes; (f) corroded for 20 minutes; Figure 5 In-situ optical microscope images of Example 1 of the present invention; (a) uncorroded; (b) corroded for 1 minute; (c) corroded for 5 minutes; (d) corroded for 10 minutes; (e) corroded for 15 minutes; (f) corroded for 20 minutes; Figure 6 Graphs of surface macroscopic morphology changes of the examples and comparative examples of the present invention. Detailed implementation manners

[0023] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with examples. Of course, the specific examples described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Example 1 I. Preparation of materials and equipment Aluminum alloy coil: An AA3003 hot-rolled aluminum alloy coil with a thickness of 1.0 mm, a coil width of 300 mm, and a linear velocity set at 5 m / min.

[0025] Raw materials for preparing the corrosion inhibitor: Sodium glutamate (analytical pure, Aladdin) Sodium glycinate (analytical pure) Sodium citrate (as an auxiliary corrosion inhibitor) Benzotriazole (BTA, analytical pure) Sodium dodecyl sulfonate (SDS, surfactant) Potassium zirconium fluoride (K2ZrF6, analytical pure) Sodium gluconate (complexing control agent) Deionized water (conductivity <1 μS / cm) II. Preparation of the corrosion inhibitor solution The solution of the adsorption and slow-release system (the first tank) is prepared as follows: Sodium glutamate: 0.12 mol / L Sodium glycinate: 0.03 mol / L (sodium glutamate: sodium glycinate = 4:1) Sodium citrate: 0.01 mol / L Benzotriazole (BTA): 0.005 mol / L Sodium dodecyl sulfonate: 0.005 mol / L pH is adjusted to 7.2 (fine-tuned with NaOH or HCl). The induced film-forming system solution (the second tank) is prepared as follows: Potassium zirconate: 0.01 mol / L Sodium gluconate: 0.005 mol / L pH is adjusted to 4.5 (fine-tuned with acetic acid / sodium hydroxide buffer solution). III. Coil processing process steps Pretreatment section (continuous coil cleaning system): Alkaline degreasing solution: 5wt% NaOH + 1wt% Na3PO4 Processing temperature: 55°C Processing time: 90 seconds Pickling solution: 1wt% HNO3 Processing time: 20 seconds Neutralization and rinsing: Rinse twice with deionized water for 10 seconds each time to ensure that the pH returns to neutral and the residual liquid is removed. Adsorption and slow-release treatment section (the first tank): Tank solution temperature: 38°C Immersion time: 90 seconds (continuous immersion) Tank solution circulation flow rate: 1 L / min to maintain a uniform concentration Induced film-forming treatment section (the second tank): Tank solution temperature: 45°C Immersion time: 45 seconds Maintain the pH at 4.5 to prevent premature precipitation of Zr ions Drying and winding section: Hot air temperature: 85°C Drying time: 3 minutes Wind speed: 3.5 m / s The coil is wound and packaged after being cooled to room temperature.

[0026] Example 2 Prepared according to the same preparation method as in Example 1, except that the main corrosion inhibitor is a mixture of sodium glutamate and sodium glycine with a concentration of 0.06 mol / L.

[0027] Example 3 Prepared according to the same preparation method as in Example 1, except that the main corrosion inhibitor is a mixture of sodium glutamate and sodium glycine with a concentration of 0.2 mol / L.

[0028] Example 4 Prepared according to the same preparation method as in Example 1, except that the concentration of the auxiliary corrosion inhibitor is 0.005 mol / L.

[0029] Example 5 Prepared according to the same preparation method as in Example 1, except that the concentration of the auxiliary corrosion inhibitor is 0.05 mol / L.

[0030] Example 6 Prepared according to the same preparation method as in Example 1, except that the concentration of potassium zirconate is 0.005 mol / L.

[0031] Example 7 Prepared according to the same preparation method as in Example 1, except that the concentration of potassium zirconate is 0.015 mol / L.

[0032] Example 8 Prepared according to the same preparation method as in Example 1, except that the concentration of potassium zirconate is 0.01 mol / L.

[0033] Example 9 Prepared according to the same preparation method as in Example 1, except that the molar ratio of sodium glutamate to sodium glycinate is 2:1.

[0034] Example 10 Prepared according to the same preparation method as in Example 1, except that the molar ratio of sodium glutamate to sodium glycinate is 5:1.

[0035] Example 11 Prepared according to the same preparation method as in Example 1, except that the treatment temperature in step (2) is 35 °C and the soaking time is 60 seconds; the treatment temperature in step 3 is 40 °C and the treatment time is 30 seconds.

[0036] Example 12 Prepared according to the same preparation method as in Example 1, except that the treatment temperature in step (2) is 40 °C and the soaking time is 90 seconds; the treatment temperature in step 3 is 50 °C and the treatment time is 60 seconds.

[0037] Example 13 Prepared according to the same preparation method as in Example 1, except that the metal coil is an AZ91 aluminum alloy coil.

[0038] Comparative Example 1 Prepared according to the same preparation method as in Example 1, except that sodium glycinate is not added to the main corrosion inhibitor and the concentration remains unchanged.

[0039] Comparative Example 2 Prepared according to the same preparation method as in Example 1, except that no auxiliary corrosion inhibitor was added.

[0040] Comparative Example 3 Prepared according to the same preparation method as in Example 1, except that the induced film-forming system solution was not used, and only the adsorption and slow-release system solution was used.

[0041] Comparative Example 4 Prepared according to the same preparation method as in Example 1, except that the adsorption and slow-release system solution and the induced film-forming system solution were placed in the same liquid tank.

[0042] Comparative Example 5 Prepared according to the same preparation method as in Example 1, except that the pH values of both the adsorption and slow-release system solution and the induced film-forming system solution were not adjusted.

[0043] Comparative Example 6 Prepared according to the same preparation method as in Example 1, except that the molar ratio of sodium glutamate to sodium glycine was 1:1.

[0044] Experimental tests: 1. Electrochemical corrosion test The electrochemical corrosion performance was tested using a three-electrode system, where the working electrode was the treated aluminum alloy coil sample (exposed area: 1 cm 2 ), the reference electrode was a saturated calomel electrode, and the auxiliary electrode was a platinum electrode. The test medium was a 3.5 wt.% NaCl aqueous solution.

[0045] First, the open-circuit potential was tested. After the potential stabilized, the potentiodynamic polarization test was carried out with a scanning rate of 1 mV / s and a potential range of open-circuit potential ± 350 mV; subsequently, the electrochemical impedance spectroscopy test was carried out with a frequency range of 10 5 Hz to 10 -1 Hz and a perturbation voltage of 5 mV. The tests were all carried out at room temperature, and at least 3 parallel experiments were performed on all samples, and the results were averaged.

[0046] 2. In-situ corrosion test Aluminum alloy coil samples were selected and etched with a 4 wt.% nitric acid alcohol solution for 3 seconds to reveal the grain boundary structure. An in-situ observation device consisting of a transparent observation cell and an optical microscope was used to record the changes in the corrosion behavior of the samples in real time in a corrosion solution (3.5 wt.% NaCl) environment. After the in-situ test, the samples were rinsed with anhydrous ethanol and dried, and the corrosion areas were located by backscattered electron mode, and the surface morphology changes were observed by scanning electron microscopy.

[0047] 3. Immersion experiment The metal coil samples before and after treatment were cut into 1 cm × 1 cm test pieces according to industrial processes, and then washed and dried with anhydrous ethanol for later use. The samples were immersed in 3.5wt.% NaCl solution for 40 h, and the macroscopic changes on the sample surface were recorded every 10 h. After immersion, the sample surface was analyzed by scanning electron microscopy.

[0048] Table 1 Polarization curve fitting data

[0049] according to Figure 1 From the test results of the polarization curve, it can be seen that Example 1 shows the best corrosion inhibition effect among all samples, with the lowest corrosion current density and the highest corrosion inhibition efficiency, indicating that a good synergy is formed between the main corrosion inhibitor and the auxiliary corrosion inhibitor, the surfactant and the induced film-forming system in its formula. In contrast, although the parameters of Examples 2 to 13 have been optimized or adjusted, they have not achieved the comprehensive corrosion inhibition performance of Example 1. This may be due to the interference of concentration deviation, molar ratio change or treatment conditions on the density and stability of the film layer, resulting in a slight decrease in the corrosion inhibition effect. A number of comparative samples all showed corrosion current densities significantly higher than those of the embodiments, among which the decrease in corrosion inhibition efficiency of Comparative Examples 1, 5 and 6 was particularly obvious, indicating that the lack of the main corrosion inhibitor, unadjusted pH or unbalanced ratio will significantly weaken the protective ability of the film layer. In addition, it can also be seen from the comparison of Comparative Example 3 with Comparative Example 4 that the existence of the induced film-forming system alone is more advantageous than the mixed treatment of the two systems, indicating that staged treatment can more effectively promote the formation of a protective film. The overall results show that the dual-tank synergistic adsorption-film-forming treatment method proposed in the present invention, combined with amino acid main corrosion inhibitor, auxiliary ligand and Zr film-forming system, significantly improves the passivation effect and corrosion resistance of the aluminum alloy surface, and has good engineering adaptability and promotion potential. Table 2 Fitting data of AC impedance spectrum

[0050] According to the AC impedance spectroscopy test results of the embodiments and comparative examples of the present invention, the performance of Example 1 is the best, manifested as the highest film resistance (Rf) and the smallest interfacial capacitance (CPEf), indicating that a dense, stable and high-impedance protective film is formed on the aluminum alloy surface. This is mainly attributed to the synergistic effect between the reasonable ratio of the main corrosion inhibitors (sodium glutamate and sodium glycine at a ratio of 4:1) and the film-forming induction system (potassium zirconate and sodium gluconate), which effectively induces the formation of a Zr-rich passivation film with a cross-linked structure. In other embodiments, when the concentration or ratio of the main corrosion inhibitor is adjusted, or the content of the auxiliary components changes, the impedance performance generally decreases, indicating a reduction in the denseness or film-forming integrity of the protective film. In addition, the results of the comparative examples show that the absence of key components (such as sodium glycine, auxiliary corrosion inhibitors or induction systems) will significantly reduce the impedance characteristics of the film and the overall corrosion inhibition efficiency, and even degrade the system to a level close to that of the blank sample. This fully demonstrates the significant advantages of the multi-factor synergistic corrosion inhibition and film-forming system designed in the present invention, and the presence of its key components and the optimal parameter combination are the core to ensure its high-efficiency protective performance. Combining the change of the ηp value can also confirm the good correlation between the impedance characteristics and the corrosion inhibition efficiency, verifying the significant improvement of the innovative system in inhibiting the corrosion of aluminum alloy.

[0051] By comparing Figure 4 the blank group Figure 5 and Example 1

[0052] From Figure 6The comparison of the immersion effects at different time periods clearly shows that, in the same 3.5 wt.% NaCl corrosive environment, the samples of the blank group, Comparative Example 3, and Comparative Example 4 all significantly show an increase in corrosion products, surface roughening, and corrosion expansion over time. Especially at 30 h and 40 h, the corrosion patches have covered a large area, and peeling and pitting morphologies even appear in some areas, indicating their weak corrosion resistance; while the surface of the sample of Example 1 changes minimally during the entire 40-hour immersion process, only showing a small number of scattered corrosion points, with good overall smoothness and no obvious corrosion patches or product coverage. Combining with the glutamate-sodium glycinate main corrosion inhibition system and the potassium zirconate induced film construction mechanism adopted in Example 1, it is inferred that it first forms a high-density organic adsorption layer on the surface to inhibit the initial oxidation reaction, and then forms a dense inorganic conversion film through Zr ion complexation for double protection, thereby effectively blocking the Cl ion erosion path and the electrochemical reaction activity of metal ions. In contrast, due to the lack of induced film construction or reasonable composition ratio in Comparative Examples 3 and 4, the protective ability of the film layer is discontinuous, and the corrosion gradually expands. Therefore, this figure verifies that the examples of the present invention can significantly improve the medium- and long-term anti-corrosion ability of aluminum alloy coils in a salt spray environment under the synergistic action of slow-release adsorption and film formation.

[0053] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. A compound corrosion inhibitor for continuous metal coils, characterized in that, The corrosion inhibitor consists of an adsorption and slow-release system solution and an induced film-forming system solution: The adsorption and slow-release system solution includes the following components: The main corrosion inhibitor is a mixture of sodium glutamate and sodium glycine, with a concentration of 0.06 - 0.2 mol / L Auxiliary corrosion inhibitor, with a concentration of 0.005 - 0.05 mol / L Inhibitor, with a concentration of 0.001 - 0.02 mol / L Surfactant, with a concentration of 0.001 - 0.01 mol / L The rest is deionized water, and the pH is adjusted to 7.0 - 7.5; The induced film-forming system solution includes the following components: Potassium zirconate, with a concentration of 0.005 - 0.015 mol / L Complexing control agent, with a concentration of 0.001 - 0.01 mol / L The rest is deionized water, and the pH is adjusted to 4.0 - 5.

0.

2. The compound corrosion inhibitor for continuous metal coils according to claim 1, wherein, The auxiliary corrosion inhibitor is one of sodium citrate, sodium malate, and sodium hypophosphite.

3. The compound corrosion inhibitor for continuous metal coils according to claim 1, wherein The inhibitor is one of benzotriazole, EDTA, and sodium tripolyphosphate; the surfactant is one of sodium dodecylsulfonate, sodium dodecylbenzenesulfonate, and cocamidopropyl betaine.

4. The compound corrosion inhibitor for continuous metal coils according to claim 1, characterized in that The molar ratio of sodium glutamate to sodium glycine is 2:1 - 5:

1.

5. A compound corrosion inhibitor treatment process for continuous metal coils, characterized in that, It includes the following steps: (1) Coil pretreatment: The metal coil is successively subjected to alkaline degreasing, acid pickling and neutralization, and deionized water rinsing; (2) Treatment with the adsorption and slow-release system solution: The coil output from step (1) enters the adsorption and slow-release system solution tank for immersion treatment; (3) Induced film formation with the induced film-forming system solution: The coil output from step (2) enters the induced film-forming system solution tank; (4) The coil output from step (3) is subjected to hot air drying, cooling, and winding.

6. The compound corrosion inhibitor treatment process for continuous metal coils according to claim 5, characterized in that, The component compositions of the adsorption and slow-release system solution and the induced film-forming system solution in the corrosion inhibitor are as shown in the component compositions of the adsorption and slow-release system solution and the induced film-forming system solution in any one of claims 1 - 5.

7. The compound corrosion inhibitor treatment process for continuous metal coils according to claim 5, characterized in that The treatment temperature in step (2) is 35 - 40 °C, and the immersion time is 60 - 90 seconds.

8. The compound corrosion inhibitor treatment process for continuous metal coils according to claim 5, characterized in that, The treatment temperature in step 3 is 40 - 50 °C, and the treatment time is 30 - 60 seconds.

9. The compound corrosion inhibitor treatment process for continuous metal coils according to claim 5, characterized in that, The hot air temperature in step (4) is 80 - 90 °C, and the wind speed is 2 - 5 m / s.

10. The compound corrosion inhibitor treatment process for continuous metal coils according to claim 5, characterized in that, The metal coil is any one of AA3003, AA5005, and AA6061 aluminum alloy coils.

Citation Information

Patent Citations

  • Zeolite loading catalyst, preparation method thereof and application thereof to organic wastewater treatment

    CN105233855A

  • Electrolyte corrosion inhibitor, aluminum-air battery electrolyte and preparation method of aluminum-air battery electrolyte

    CN105870545A

  • Environment-friendly organometallic corrosion inhibitor and preparation method and application thereof

    CN110819992A

  • Film-forming corrosion inhibitor suitable for nuclear power unit in operation and application method of film-forming corrosion inhibitor

    CN113699530A

  • Oxidizing catalyst

    JP1993049943A